To develop online platform and determine its effectiveness in ENHANCING DIABetes knowledge among diabetes patients in primary CARE clinic (Enhancing-Diab-Care Study): Study protocol - Hui Zhu Thew; Ai Theng Cheong; Sazlina Shariff Ghazali; Poh Ying Lim; Aneesa Abdul Rashid; Ping Foo Wong; Yong Kui Choon; Adam Firdaus bin Dahlan; Chitra Suluraju; Nadiah Othman; Yong Wai Leng; Izwan Zuhrin bin Abdul Malek; et al. (PLoS ONE, 2025)
Diabetes Mellitus (DM)- Type 2 is increasingly prevalent in today’s population. DM remains poorly controlled due to insufficient knowledge and understanding of this disease. Maintaining good diabetic self-care requires knowledge and empowerment. The COVID-19 pandemic had caused a shift of some public attention from non-communicable to communicable diseases, leading to patients becoming ignorant of their diabetic status. Therefore, we aim to develop an online education video platform that enables patients to enhance their knowledge about Diabetes Mellitus Type 2. In this blocked randomised control trial, a minimum number of 232 participants with type 2 diabetes mellitus will be needed. Patients will consent and voluntarily participate during their follow-up at public primary health care clinic (Klinik Keshihatan Cheras Baru). Patients undergoing diabetic follow-up will be divided into two groups where only patients within the intervention group will receive diabetic care video. Patients’ clinical profiles such as date of birth, gender, education status, Diabetes Knowledge Test (DKT) and Diabetic Empowerment Scale (DES-28) were collected to assess diabetes self-care knowledge and empowerment using self-administered questionnaires. Patients will be reminded to complete the educational video at the 3-month and 6-month follow-ups, and the aforementioned parameters will be reassessed. The data will be assessed using an independent t-test for the difference between intervention and control groups. A Paired t-test will assess the difference between the patient pre and post-intervention after 6 months. A generalised Estimating Equation will be used to investigate the effectiveness of diabetes knowledge and clinical outcome, adjusted with covariates. P < 0.05 will be considered statistically significant. Ethical principles outlined in the Declaration of Helsinki and Malaysian Good Clinical Practice Guideline will be followed. Ethical approval will be obtained from MREC and NMRR before starting any study-related activities.